Narracja filmowa – funkcja terapeutyczna. Kilka słów o Amatorze (1979) Krzysztofa Kieślowskiego - Grodź, Iwona (Człowiek i Społeczeństwo, 2023)
The strategy of the (auto)therapist in film art is a process of dynamic interaction between the transmitting and receiving roles, i.e. the director – the protagonist of his work and the projected viewers. The film is a space enabling the creator to analyze the problems of a modern man in order to increase the skills of self-understanding, self-distancing from emotions and developing reflection. The latter is conducive to the coherence of narratives about oneself and the construction of one’s identity. Results and conclusions: Projection and identification, which is part of the emotional and cognitive responses available to the creator and recipient of the work, are processes of therapeutic importance. Creation (and contact with its effect – a finished work) is then a tool helping to regulate: modulation of attention, emotions (modulation of emotion), fosters cognition (modulation of cognition), understanding behavior (modulation of behavior) and communication (modulation of communication).